Hubungan Pengetahuan Bahaya Paparan Sinar Matahari Dengan Perilaku Penggunaan Sunscreen Pada Mahasiswa Kepelatihan Kecabangan Olahraga Universitas Negeri Jakarta - Annisa Rusyda Hakim; Nurina Ayuningtyas; Dwi Atmanto (Journal on Education, 2024)
This study investigated the relationship between sports coaching students' knowledge of the dangers of sun exposure and sunscreen use behavior. Data were collected through a knowledge test and behavior questionnaire conducted on 38 students through purposive sampling technique. The results show that students have knowledge about the dangers of sun exposure with a mean value of 7.74 and a mean value of sunscreen use behavior of 52.61. The linearity test analysis results showed a significant linear relationship between knowledge and behavior (p = 0.949). In the partial test (t-test) the result obtained is a significance value of 0.760. Therefore, it can be concluded that 0.760 > 0.050 which indicates that Ho is accepted and Ha is rejected, meaning that the independent variable (X) has no significant relationship with the dependent variable (Y). Through the coefficient of determination test, a value of 0.003 was obtained, which means that the relationship between variable X (knowledge of the dangers of sun exposure with variable Y (behavior of using sunscreen on sports coaching students) only contributed 0.3%. While the remaining 99.7% is another factor not examined in this study. The findings in this study suggest the need to increase education to increase student awareness of the importance of protecting themselves from UV exposure.